2000
DOI: 10.2139/ssrn.144408
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Mechanism for the Efficient Provision of Public Goods - Experimental Evidence

Abstract: The author reports on a series of experiments designed to investigate the factor of incentive mechanisms in the case of private provisions of public goods. In the Control treatment, there was no mechanism so that subjects faced strong free-riding incentives. In the so-called Falkinger mechanism treatment, the author implemented the Falkinger mechanism. The studies explored the impact of the mechanism in different economic environments. Results showed that the proposed incentive mechanism is very promising. Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(167 citation statements)
references
References 46 publications
6
160
1
Order By: Relevance
“…Centralized punishment can even be effective if it is not deterrent (Engel 2013). Falkinger, Fehr, Gächter, and Winter-Ebmer (2000) showed that an exogenously given tax-subsidy mechanism induces people to cooperate in line with theoretical predictions about how the incentives should work. Another line of research, dating back to a seminal paper by Toshio Yamagishi (1986) showed that people are also willing to contribute to a "punishment fund" (think of funding law enforcement through people's taxes) to punish lowest contributors.…”
Section: The Determinants Of Social Order Iii: Punishment and Other Imentioning
confidence: 71%
“…Centralized punishment can even be effective if it is not deterrent (Engel 2013). Falkinger, Fehr, Gächter, and Winter-Ebmer (2000) showed that an exogenously given tax-subsidy mechanism induces people to cooperate in line with theoretical predictions about how the incentives should work. Another line of research, dating back to a seminal paper by Toshio Yamagishi (1986) showed that people are also willing to contribute to a "punishment fund" (think of funding law enforcement through people's taxes) to punish lowest contributors.…”
Section: The Determinants Of Social Order Iii: Punishment and Other Imentioning
confidence: 71%
“…3 As an anecdote, I wrote an software module for an experimental software implementing a mechanism in public good experiments (Falkinger et al, 2000). Since the researchers wanted to have a lot of flexibility in the information conditions, I had to program a dialog with more than 80 checkboxes.…”
mentioning
confidence: 99%
“…This contrasts with, for example, money demand studies, for which unambiguous data are available on an euro area level only as of January 1999. 3 Second, the model has been used as a workhorse for many policy discussions and applied to a large number of countries so that it has proven its ability in applied policy analysis and is well known in the profession. Finally, our choice to use this nutshell model is guided by the objective of this paper, namely to study the term structure in a macroeconomic context characterised by substantial structural institutional change.…”
Section: Modelling the Term Structurementioning
confidence: 99%